The African American journey to the power dome : Wright, Ellison, Baldwin - Sharma, Bhumika (Cambridge Scholars Publishing, 2018)
How far has the American Dream been accessible to black characters in African American literature? The answer to this question requires a deep probing of the emotional and ideological patterns delineated in Black American narratives. This book traces the African American journey from the plantation to the power dome through multiple socio-artistic perspectives of Black American authorship. It captures numerous referential inventions ranging from the 'colored' to the 'Black American, ' while throwing light on the transforming status of America's Native Son, the marked visibility of its Invisible.